Response of fatal landslides to precipitation over the Chinese Loess Plateau under global warming - Guan, Xiaodan; Sun, Wen; Kong, Xiangning; Zhang, Fanyu; Huang, Jianping; He, Yongli (Frontiers in Earth Science, 2023)
Rain-induced loess landslides are especially prevalent in the Chinese Loess Plateau (CLP). Some became fatal landslide disasters, leading to numerous casualties and significant socioeconomic losses. Extreme precipitation is the main cause of landslide occurrence. Therefore, in this study we discuss the correlation between seven extreme precipitation indices, single continuous precipitation events and fatal landslides in the CLP using Pearson correlation analysis. We also predict future precipitation under climate changes using five optimal CMIP6 models. During the period 2004–2016, fatal landslides in the CLP increased at a rate of 0.6 per year, with frequent landslide events occurring especially in the central and southwestern parts of the CLP. We find that SDII (simple daily intensity precipitation index) and R×5day (max 5-day precipitation amount) show spatial distribution that are consistent with fatal landslides. Extreme precipitation events were frequent after year 2000; and several extreme precipitation indices show an increasing trend with a higher magnitude since 2000 than before 2000. In particular, in 2013 when the number of fatal landslides was as high as 17, SDII, R95pTOT (extremely wet days), R25mm (very heavy precipitation days), and R×5day all showed abrupt increases. Single continuous precipitation events have profound effects on fatal landslides. We show that single continuous precipitation events with cumulative precipitation of 185–235 mm and duration of 6 days or longer have the highest correlation with fatal landslides. As the increasing occurrence of extreme rainfall events by the global warming, the CLP may face more fatal landslides in the future, especially in the high emission scenario of greenhouse gases (GHGs).